2021
DOI: 10.20414/transformasi.v17i2.3999
|View full text |Cite
|
Sign up to set email alerts
|

Sosialisasi pelestarian pencak silat sebagai warisan budaya dan soft power indonesia

Abstract: [Bahasa]: Pencak silat merupakan warisan nasional negara Indonesia yang perlu dikenal dan dilestarikan oleh generasi muda. Oleh karenanya, diperlukan upaya masif untuk mengenalkan pencak silat kepada generasi muda yang salah satunya melalui kegiatan sosialisasi. Kegiatan pengabdian kepada masyarakat ini berbentuk sosialiasasi yang bertujuan untuk memberikan pengetahuan dan pemahaman terhadap siswa sekolah menengah pertama tentang pentingnya pencak silat sebagai warisan budaya sekaligus sumber soft power Indone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
3
0
4
Order By: Relevance
“…Nationally, Langga is rarely covered by major media in Indonesia, in contrast to Pencak silat which has often been covered by major Indonesian media about his achievements [11]. But that does not mean that Langga does not have fans, it is also proven that many respondents have an interest in learning the Langga martial arts (Fig.…”
Section: Do You Want To Learn Martial Arts?mentioning
confidence: 99%
“…Nationally, Langga is rarely covered by major media in Indonesia, in contrast to Pencak silat which has often been covered by major Indonesian media about his achievements [11]. But that does not mean that Langga does not have fans, it is also proven that many respondents have an interest in learning the Langga martial arts (Fig.…”
Section: Do You Want To Learn Martial Arts?mentioning
confidence: 99%
“…Aktor non negara merespon secara personal terkait dengan arti hubungan antar negara dan mempengaruhi opini publik internasional (Rachmawati, 2016). Non state actor di dalam diplomasi publik diantaranya Non-Government Organization (NGO), Multinational Corporations (MNC), masyarakat atau rakyat dan individu (Rachman et al, 2019;Rachmawati, 2016). Pada dasarnya keberadaan non state actor secara tidak resmi mewakili negara.…”
Section: B Diplomasi Publikunclassified
“…Diplomasi publik memerlukan alat atau media untuk dapat menyampaikan citra atau pesan-pesan terkait dengan negara. Salah satunya melalui perhelatan acara olahraga berskala internasional seperti Asian Games (Rachman et al, 2019). Hal ini dikarenakan olahraga dapat dimanfaatkan sebagai alat untuk meningkatkan citra suatu negara di mata publik internasional.…”
Section: B Diplomasi Publikunclassified
See 1 more Smart Citation
“…generally, the network used is the internet. Rachman et al, (2020) stated that e-sports is a sport that is competed in major international sports events such as the Olympics. It is further revealed that someone who is involved in sports, is an expert in sports and is involved in sports, and is seriously involved in various activities in e-sports is called an athlete.…”
Section: Introductionmentioning
confidence: 99%